Mutagenicity and clastogenicity potential of chlorinated drinking water from Metro Manila and other cities in the Philippines - Lim-Sylianco, C.Y.; Villaseñor, I.M.; Torralba, R.; Guevara, A.P. (1986)
Mutagenicity and clastogenicity potential of chlorinated drinking water from Metro Manila and other cities of the Philippines were studied. Rec assay was used to study the DNA damaging capacity before metabolic activation. The host-mediated assay was utilized to determine the mutagenicity potential after metabolic activation and the micronucleus test was employed to study the genotoxic effects on bone marrow erythrocytes. None of the chlorinated water samples exhibited DNA damaging potential before metabolic activation. Mutagenic effects were not observed after metabolic activation and no genotoxic effects were shown in bone marrow erythrocytes. Hexane extracts of selected water samples were also studied. These were not mutagenic before and after metabolic activation and no chromosome breaking effects were observed.
Includes bibliographical references (pages 246-247)
Keywords: Chemistry; Water, Chlorinated drinking -- Mutagenic and clastogenic properties